2016
DOI: 10.1136/bmjopen-2016-011671
|View full text |Cite
|
Sign up to set email alerts
|

Association between passive smoking and mental distress in adult never-smokers: a cross-sectional study

Abstract: ObjectiveMany studies have suggested exposure to secondhand smoke (SHS) is a risk factor for various somatic diseases, but only few studies based on small sample size or specific groups have explored the association between passive smoking and mental distress. We performed this study to examine the relationship between passive smoking and mental distress in adult never-smokers of north-east China.MethodsMultistage, stratified random cluster sampling design was used in this cross-sectional study in 2012. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The positive association between SHS exposure and mental health may be explained as integrating biological and epidemiological aspects [ 7 , 17 , 18 , 31 ]. The positive association between SHS exposure and mental health may be explained as integrating biological and epidemiological aspects [ 1 , 21 , 22 , 31 , 32 , 33 ]. Some studies have reported that exposure to SHS in stressful states for a long time is related to the risk for negative lifestyle and behavioral problems such as emotional and conduct disorders at a young age [ 21 , 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The positive association between SHS exposure and mental health may be explained as integrating biological and epidemiological aspects [ 7 , 17 , 18 , 31 ]. The positive association between SHS exposure and mental health may be explained as integrating biological and epidemiological aspects [ 1 , 21 , 22 , 31 , 32 , 33 ]. Some studies have reported that exposure to SHS in stressful states for a long time is related to the risk for negative lifestyle and behavioral problems such as emotional and conduct disorders at a young age [ 21 , 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between SHS exposure and mental health may be explained as integrating biological and epidemiological aspects [ 1 , 21 , 22 , 31 , 32 , 33 ]. Some studies have reported that exposure to SHS in stressful states for a long time is related to the risk for negative lifestyle and behavioral problems such as emotional and conduct disorders at a young age [ 21 , 22 , 31 ]. A negative lifestyle, manifest in lifestyle aspects such as physical exercise, eating habits, and sleep patterns, can exacerbate mental health problem [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors: A smoker was defined as a person who smoked at least one cigarette per day within the last 30 days, and drinker was a person who consumed more than one alcoholic drink per week. Participants were divided into those that “sometimes exercise”, with an exercise frequency of one or two times a week; those who exercised more than three times a week were defined as “exercise frequently”; while those who didn’t or seldom exercised were defined as those that “never or rarely exercise” 18 .…”
Section: Methodsmentioning
confidence: 99%